2021
DOI: 10.1055/a-1587-9336
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of Vitamin D Receptor and the Effect on Metabolic and Endocrine Abnormalities in Polycystic Ovary Syndrome: A Review

Abstract: Polycystic ovary syndrome (PCOS) is one of the most prevalent endocrine disorder in women of reproductive age. Vitamin D and its receptor are thought to play an important role in PCOS susceptibility, although the impact of vitamin D receptor (VDR) polymorphisms on the hormonal and metabolic profile is still controversial. A literature search in PubMed and Embase was performed up to September 2020 for case-contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…There is a vitamin D response element in the promoter region of the insulin gene, and vitamin D receptor polymorphisms have been studied as a proposed cause for the relationship between vitamin D serum levels, insulin resistance and hyperandrogenism [38]. A recent review article concluded that the ApaI polymorphism specifically was associated with hyperandrogenism in Asian and white populations, while the FokI polymorphism was associated with metabolic and endocrine disturbances primarily in the Asian population [39].…”
Section: Vitamin D and Polycystic Ovarian Syndromementioning
confidence: 99%
“…There is a vitamin D response element in the promoter region of the insulin gene, and vitamin D receptor polymorphisms have been studied as a proposed cause for the relationship between vitamin D serum levels, insulin resistance and hyperandrogenism [38]. A recent review article concluded that the ApaI polymorphism specifically was associated with hyperandrogenism in Asian and white populations, while the FokI polymorphism was associated with metabolic and endocrine disturbances primarily in the Asian population [39].…”
Section: Vitamin D and Polycystic Ovarian Syndromementioning
confidence: 99%
“…All of this information, along with the reported key role of VDR in the regulation more than 3% of the human genome, prompted researchers to examine the real contribution of the VDR gene polymorphisms in metabolic and endocrine disturbance of PCOS [ 21 , 22 ]. Despite some evidence pointing to an influence of VDR gene variants in PCOS features, it is difficult to definitively establish a clear association of VDR polymorphisms with the development of PCOS [ 23 ].…”
Section: Vitamin Dmentioning
confidence: 99%
“…Polymorphisms in the Vitamin D receptor (VDR) have been linked to some of the clinical representations associated with PCOS (Reis et al, 2017). The gene is highly polymorphic, and its polymorphic markers namely FokI, BsmI, ApaI, TaqI, Tru9I, and Cdx2 have resulted in aslew of allelic variants that vary among ethnic groups (Vulcan et al, 2021). A previous meta-analysis with nine studies reported in 2019 has found the association of VDR ApaI (rs7975232) (C > A) gene polymorphism and PCOS outcome (Shi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%